TEOS Silane Film Modified with SBA-15 Loaded with Cocoa Husk Extract as Pretreatment of ASTM 1008 Steel - Iago M. F. C. R. e Silva; Gabriel A. Carrijo-Gonçalves; Lhaira S. Barreto; Luiz Carlos Salay; Glória M. Vinhas; Idalina V. Aoki; Miriam S. Tokumoto; Vera R. Capelossi (Materials Research, 2024)
Research on eco-friendly methods led to the investigation of natural inhibitors and silane films modified with nanostructured mesoporous silica (SBA-15), a molecular sieve that can carry molecules with inhibitory properties. Combining natural extracts such as cocoa husk with SBA-15 aims to develop an enhanced silane-based pretreatment. This involves obtaining an alcoholic extract, and then mixing it with SBA-15 to modify the silane film. Different concentrations (1%, 2%, and 3%) of SBA-15 loaded with extract were prepared. Electrochemical tests, especially electrochemical impedance spectroscopy (EIS), in a 0.1 mol/L NaCl solution, revealed improved corrosion resistance with the tetraethylorthosilane (TEOS) film modified using 3% SBA-15 loaded with extract. Scanning electron microscopy showed the film and SBA-15 on the steel surface, while Fourier transform infrared spectroscopy identified functional groups characteristic of SBA-15, pure or loaded, and silane film. Therefore, it was possible to enhance the TEOS silane film by adding SBA-15 loaded with plant residue extract.